Linking work environment to employee performance: the mediating role of work discipline - Achmad Sani Supriyanto; Vivin Maharani Ekowati; Hilda Vironika (Universitas Negeri Surabaya, 2020)
This study aims to examine the influence of the work environment on employee performance mediated by work discipline. It is quantitative research with questionnaires as the data collection method. Data were analyzed by using Path Analysis. The populations are all of the full-time employees, and seventy-eight respondents of them were selected by saturated sampling method. The study shows that the work environment affects employee performance, and work discipline mediates the effect of the work environment on employee performance.